Honey bee attractants and pollination in sweet orange, Citrus sinensis (L.) Osbeck, var. Pera-Rio - Malerbo-souza, D. T.; Nogueira-couto, R. H. [UNESP]; Couto, L. A. (Centro de Estudos de Venenos e Animais Peçonhentos, 2004)
This experiment studied the frequency and behavior of insects on sweet orange flowers, Citrus sinensis (L.) Osbeck, their effect on fruit production (quantity and quality), nectar and pollen collection, and the effectiveness of different attractants. Over three consecutive years, the most frequent visitor to the flowers was Apis mellifera (Africanized). Flowers visited less than ten times showed low fructification. Fruit production was 35.30% greater in uncovered flowers. Fruit mean weight was much greater in uncovered (180.2g) than in covered flowers (168.5g). Fruits from the covered were more acid (1.411g of citric acid/100ml of juice) than the uncovered flowers (1.164g of citric acid/100ml of juice). The number of seeds per bud was higher in the uncovered (1 seed/bud) than in the covered treatment (0.8 seed/bud). Bee-HereR, eugenol, geraniol, citral, and lemon grass extract, mainly diluted in water, were effective in attracting honeybees to orchards. However, these compounds were less effective when diluted in sugar syrup. The same products had variable attractiveness to honeybees in different years.
Keywords: attractants; Citrus sinensis var. Pera-Rio; pollination; Apis mellifera